Functional and Nutraceutical Significance of Amla (Phyllanthus emblica L.): A Review - Maryam Gul; Zhi-Wei Liu; Iahtisham-; Roshina Rabail; Fatima Faheem; Noman Walayat; Asad Nawaz; Muhammad Asim Shabbir; Paulo E. S. Munekata; José M. Lorenzo; Rana Muhammad Aadil (MDPI AG, 2022)
Phyllanthus emblica L. (also popularly known as amla) is a tree native to the India and Southeast Asia regions that produces fruits rich in bioactive compounds that could be explored as part of the increasing interest in naturally occurring compounds with biological activity. Thus, this review aims to highlight the nutritional aspects, rich phytochemistry and health-promoting effects of amla. Scientific evidence indicates that polyphenols are central components in fruits and other sections of the amla tree, as well as vitamin C. The rich composition of polyphenol and vitamin C imparts an important antioxidant activity along with important in vivo effects that include improved antioxidant status and activity of the endogenous antioxidant defense system. Other potential health benefits are the anti-hyperlipidemia and antidiabetic activities as well as the anticancer, anti-inflammatory, digestive tract and neurological protective activities. The promising results provided by the studies about amla bioactive compounds support their potential role in assisting the promotion of health and prevention of diseases.